Committing communication strategy and its role in crisis management - a theoretical approach - Karoui, Anis (Journal of Risk and Crisis Management, 2021)
Facing crises exacerbation, researchers have formulated various communication strategies to control them. Focusing on the importance of the institution's commitment to its responsibility, many strategies aim to implement measures to reduce damages and to prevent the recurrence of the same mistakes causing crisis. In this paper, we formulate a new strategy named "Committing Communication Strategy", which represents an intersection between media and communication science on the one hand and sociology on the other hand in order to formulate a theoretical framework. We use the deductive approach based on theories determining communication strategies in crisis management also, by reference to some experiences that relied on committing communication allowing firms to get out of their crises and even seize their opportunities, which enabled them to rebuild and to be distinguished.
Keywords: Crisis management; Crisis communication; committing communication strategy